A Self-Orgnizing Model for Peer-to-Peer Systems using Trust Relations - Mahajan, Sourabh S.; Pathan, S.K. (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2014)
Peer-to-Peer systems enables the interactions of peers to accomplish tasks. Attacks of peers with malicious can be reduced by establishing trust relationship among peers. In this paper we presents algorithms which helps a peer to reason about trustworthiness of other peers based on interactions in the past and recommendations. Local information is used to create trust network of peers and does not need to deal with global information. Trustworthiness of peers in providing services can be describedby Service metric and recommendation metric. Parameters considered for evaluating interactions and recommendations are Recentness, Importance and Peer Satisfaction. Trust relationships helps a good peer to isolate malicious peers.